Assessment of timber supply under alternative futures - Mozgeris, G.; Brukas, Vilis; Stanislovaitis, Andrius; Kavaliauskas, Marius; Linkevičius, Edgaras (Natural Resources Institute Finland, Luke, 2016)
The aim of the study is to simulate forest management behaviour for five decades (since 2013) under different qualitative scenarios taking into account the diversity of behaviour by forest owners and managers. Simulations reveal increasing timber production costs, incomes and net profits under all scenarios. Research results could be integrated in decision processes related to forestry considering types of the forest manager and provide many possible threads for future studies.
Keywords: forest management; scenarios; modelling; economic assessment